MODERN TYPES OF EDUCATIONAL VIDEOS AND PECULIARITIES OF THEIR USE IN THE EDUCATIONAL PROCESS - Vember, Viktoriia P.; Buchynska, Dariya L. (Educological discourse, 2016)
The article considers the major changes in teaching activity that are connected with a peculiarities perception of data and information by Net-generation; the multimedia content, which is used in the preparation of teachers for different learning activities was analyzed; the peculiarities of various types of training videos were examined.